Islamic Counseling in the Digital Space: Opportunities and Ethical Challenges for Improving Family Well-Being - Samhariyyah, Rosya; Puspita, Yuwana Dwi; Nabilah, Amirotun (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
Abstrak: Digital technology has transformed the way humans interact, including in the field of counseling. In Indonesia, with internet penetration exceeding 78%, the digital space offers vast opportunities for the development of Islamic counseling that supports the well-being of Muslim families. This study used a qualitative approach based on literature review (2019–2025) to explore the ethical opportunities and challenges of digital Islamic counseling. The results indicate that digital counseling can expand access, provide flexible methods, protect client privacy, and support family programs such as Islamic parenting and conflict management. However, ethical challenges remain, including data security, limitations of non-verbal communication, counselor legitimacy, and compliance with Islamic principles. This study suggests that digital Islamic counseling can strengthen family communication, address modern parenting issues, and reinforce moral-spiritual values. Therefore, digital Islamic counseling has the potential to become an effective, ethical, and sharia-compliant family counseling model in the digital era. Kata Kunci: Islamic Counseling; Digital Counseling; Family Well-being